Green backlash and right-wing populism - Valentina Bosetti; Italo Colantone; Catherine E. de Vries; Giorgio Musto (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2025)
This narrative review delves into the politics of climate policy, with specific focus on the socalled "green backlash". That is, rising resistance by voters, parties, and governments to the climate transition. We start by reviewing the literature on the political consequences of climate policies. The evidence points to a green backlash among citizens negatively affected by the decarbonization transition. Populist right forces emerge as main beneficiaries of the backlash. They tend to be more skeptical regarding anthropogenic climate change and less supportive of climate policies. Their electoral success has negative implications for countries' climate policy making and performance. Finally, we draw insights from the literature to reflect on what can be done to improve the political sustainability of climate policies.
Keywords: 330; Climate policies; green backlash; right-wing populism